Total Synthesis of Phellinus ribis Glycans with Immunostimulating Activities by an Orthogonal One-Pot Glycosylation Strategy - Wan, Jie; Wang, Leilei; Xiao, Guozhi (Synlett, 2022)
A total synthesis of nonasaccharide repeating units and shorter sequences from Phellinus ribis glycans with strong immunostimulating activities was achieved by an orthogonal one-pot glycosylation strategy based on an N-phenyltrifluoroacetimidate glycosylation, a Yu glycosylation, and an ortho-(1-phenylvinyl)benzoate glycosylation. The issues inherent to thioglycosides-based orthogonal one-pot glycosylations, such as aglycone transfer, are eliminated by this one-pot glycosylation strategy, which streamlines the chemical synthesis of glycans.
Keywords: Phellinus ribis; glycans; one-pot reaction; glycosylation; total synthesis; oligosaccharides